Flora in a Bee-dropping-"ocean in a Drop" - Vaid, K. M (Indian Forester, 1973)
In the process of collecting nectar from the flowers, the bees also reed upon the pollen. During the course of their flight from the orchard back to the comb their excreta is dropped all along the way. The droppings, if collected and examined under the microscope, will reveal a wealth of information about the flora of the vicinity and at times, unravel mysteries. In this experiment, the presence of a single ’unknown’ walnut tree Juglans regia was detected in a virtual forest of hundreds of indigenous and exotic species growing in a estate where their enumeration figure touched over a lakh of other trees.